Study and analysis of different contact materials for ohmic RF MEMS switch - Raihanah Abdul Razak (2011)
MicroElectroMechanical Systems (MEMS) are integrated micro devices or systems combining electrical and mechanical components that can sense, control, and actuate on the micro scale and function individually or in arrays to generate effects on the macro scale. MEMS is one of the most promising areas in future computer and machinery, the next logical step in the silicon revolution. Fabricated using Integrated Circuit (IC) compatible batch-processing techniques, the small size of MEMS opens a new line of exciting applications. Reliability is of concern if MEMS machinery is used in critical applications. MEMS technology is still in its infancy, like IC technology 30 years ago. Focus has been put in wafer level reliability, the same path taken in the IC technology. Presently how MEMS fail is still not well understood. Study and analysis of contact behavior of ohmic RF MEMS switch are investigated in this project. Using a piezoactuator, with a metal tip mounted on it, and a gold wafer is used to conduct the ohmic contact instead of fabrication of MEMS switch. Data are collected to observe the transition period during contact-making process. Statistical analysis through amplitude histogram is performed. The current and contact resistance is also being analyzed to observe the phenomenon during the contact-making process. In addition, wafers of different roughness are tested and results have shown that the rougher the surface, the longer the transition period and the more fluctuations it has.